Gas Chromatographic-Flame Photometric Detection of Organophosphate Pesticide Residues and Its Application in Real Vegetable and Fruit Samples from Chiang Mai City, Thailand - Watcharapol Polyiem (Science Faculty of Chiang Mai University, 2019)
Analysis of pesticide residues is usually limited by expensive analytical apparatus and trained laboratory scientist. We developed a method for detecting 20 organophosphate (OP) pesticide residues in vegetable and fruit matrices using gas chromatographic- flame photometric detection. OP pesticide residues were extracted from well-homogenized vegetable or fruit samples using acetonitrile and clean-up with graphite carbon black solid phase extraction. The clean OP residues’ extract was finally dissolved in ethyl acetate and analyzed by GC-FPD. Mean recovery (±SD) of 20 OP pesticides was 92.9 (±10.8) % and individual mean ranged from 76.8 % (methamidophos) to 114 % (triazophos). Limits of detection of 20 OP pesticides ranged from 0.0003 mg/kg (diazinon) to 0.015 mg/kg (azinphos-methyl) which are well below the Codex maximum residue limits (MRLs). In addition, determination of 20 OP pesticides in the present method has proven to be suitable for detecting OP residues in Thailand food safety policy since major imported active OP pesticides were already covered.